Advances in cognitive systems - Nefti-Meziani, Samia; Gray, J. O. 1937- (London, United Kingdom The Institution of Engineering and Technology, 2010)
The book has 17 chapters and deals with the following subjects: cognitive robotics system; adaptive systems; dynamical enactive cognitive architecture; cooperative decision model; virtual humans; neurocomputational cognitive architectures; robotic agents; neural networks; investor behavior; swarm intelligence techniques and distributive cognition.
Electronic reproduction.
Keywords: Cognitive science; Artificial intelligence; Reasoning; Electronic books